A Critical Review on The Law of Cina Buta (Chinese Blind) According to Shaykh Abdul Qadir Bin Abdul Muthalib Al Mandili Al Indonesia Al Shafi'i - Wardi, Syah; Arif, Zuhri (DIKTUM: Jurnal Syariah dan Hukum, 2023)
Through the fiqh ideas of Shaykh Abdul Qadir bin Abdul Muthalib Al Mandili Al Indonesi Al Syafi'i, which are found in his book Al-Asadul Ma'ar Liqatil Taisil Musta'ar: on China Buta Law, this research seeks to understand how the law of marriage with the phrase nikah cina blind works. Additionally, the authors proposed that the difficulty in this study is First, how Shaykh Abdul Qadir Bin Abdul Muthalib Al Mandili Al Indonesi saw China Buta Law from a fiqh perspective. Second, how is the law's application handled when there is a china blind legal issue. This research employed library research as the primary method of investigation. and use a qualitative strategy. This is so because word descriptions serve as both the data source and the research output in the research library. The findings of this study were drawn from a study of the book Al-Asadul Ma'ar Liqatil Taisil Musta'ar: On China Buta Law, which was conducted by Shaykh Abdul Qadir bin Abdul Muthalib Al Mandili Al Indonesi Al Syafi'i. Therefore, it can be stated that Sheikh Abdul Qadir rejected and forbade the practice of Chinese blind marriages by providing a very clear justification in this regard